Kajian Model Pembelajaran SAVI Terhadap Mathematical Connections Ability - I Putu Suardipa (STAHN Mpu Kuturan Singaraja, 2020)
Mathematical connection is one of the abilities that is the goal of learning mathematics. Mathematical connections occur between mathematics and mathematics itself or between mathematics outside mathematics and between mathematics and everyday life. With the ability to connect mathematics, in addition to understanding the benefits of mathematics, students are able to see that mathematical topics are interrelated. Mathematical Connections Ability is important but students who master mathematical concepts are not necessarily smart in connecting mathematics. The SAVI learning model involves activities and connections of the body and the five senses, so that the learning that is carried out gives an effective and efficient impact on classroom management to be better. Students' memories of the material learned are stronger because students build their own knowledge of mathematical concepts and are able to connect the knowledge formed. Keywords: Mathematics, SAVI, Learning, Students